Novel Algorithm to Generate Hydrogen-Disordered Ice Structures - Matsumoto, Masakazu; Yagasaki, Takuma; Tanaka, Hideki (Journal of chemical information and modeling, 2021)
We propose an efficient algorithm for generating hydrogen-disordered ice networks utilizing graph theory and the topological characteristic of the network. The computational efficiency with the new algorithm is much higher than the conventional ones developed by Rahman and Stillinger and Buch et al. The difference in the computational time between our algorithm and either of the two conventional ones increases with increasing the system size.